Detection of non-tuberculous mycobacteria in native wildlife species at conservation risk of Argentina - Barandiaran, Soledad; Ponce, Loreana; Piras, Indiana; Rosas, Ana Carolina; Peña Martinez, Jorge; Marfil, María Jimena (Frontiers in Veterinary Science, 2024)
Nontuberculous Mycobacteria (NTM) are mainly environmental but can cause opportunistic infections and diseases in humans and animals. Livestock and wild animals can be infected with NTM. In Argentina, there are native wild species facing conservation risks, and they are the focus of protection and reintroduction projects designed to preserve biodiversity in various ecoregions. The aim of this study was to reportidentify the presence of NTM in samples collected from four endangered native wild species from nine Argentine provinces, as part of their pre-release health assessment. A total of 165 samples from giant anteater (11), peccary (104), tapir (19) and pampas deer (31) were obtained, these included either bronchoalveolar or endotracheal lavages, or oropharyngeal, nasopharyngeal or tracheal swabs. and bBacteriological culture followed by molecular identification and sequencing were performed. A total of 27 NTM were detected, including Mycobacterium avium subsp. hominissuis, M. intracellulare, M. terrae, M. gordonense, M. kumamotonense; M. fortuitum; M. saskatchewanense and M. genavense. Results revealed a 16,36% NTM recovery rate, with the giant anteater showing the highest prevalence among the mammals under study. In Argentina, due to extensive production systems, the interaction between domestic and wild species sharing the same environment is frequent,. increasing the exposure of all the species to these NTM. In this way, the transmission of infectious agents from one to another is feasible. Moreover, NTMs might interfere with the diagnosis of bovine tuberculosis and paratuberculosis. These findings emphasize the importance of active health surveillance in conservation programs. It highlights the need for an interdisciplinary approach to address NTM epidemiology in wildlife and its impact on conservation and public health. Con formato: Español (Argentina) Con formato: Español (Argentina) Con formato: Español (Argentina) Con formato: Español (Argentina) Con formato: Español (Argentina) Con formato: Español (Argentina)